ANALISIS PERBANDINGAN PARADIGMA PENDIDIKAN ISLAM DAN PENDIDIKAN BARAT - Sulthon El Hasbi Rambe; Taufik Abdillah Syukur (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2024)
This research aims to compare the objectives of Islamic education and Western education. In the context of globalization and rapid social change, this comparison becomes important to understand the differences in approaches and philosophies behind these two education systems. The research method used is comparative analysis, collecting data from various relevant sources on the objectives of Islamic education and Western education. In the process of analysis, the researcher examines the differences in perspectives on educational objectives, both from religious and secular viewpoints.The findings of the research indicate that the objectives of Islamic education emphasize the development of spirituality, morality, and the afterlife, while the objectives of Western education are more focused on intellectual development, critical thinking skills, and preparation for life in this world. Although there are fundamental differences between these two objectives, there are also some similarities, such as individual empowerment and the improvement of quality of life. This research provides valuable insights into the differences in approaches and objectives of Islamic education and Western education. In the context of an increasingly interconnected world, a better understanding of these differences can help us create an inclusive and holistic educational approach that combines the best values and policies from both education systems.